Methionine as a Spacer between Poly Acrylic acid and Ampicillin - Baghdad Science Journal (مجلة بغداد للعلوم)
In this work a novel drug delivery system through modification of poly acrylic acid with Methionine as a spacer between the poly acrylic acid which was converted to its acyl chloride and reacted with Methionine as spacer unit which has been reacted with Ampicillin drug. In vitro drug release study had been conducted successfully in basic medium in pH 7.4 and acidic medium in pH 1.1 at 37?. Due to many problems associated with drug release and, this modification could decrease the side effect of drug. The prepared prodrug polymer was characterized by spectra method [FTIR and 1H?NMR]. Physical properties and intrinsic viscosity of drug polymer were determined. The good results were obtained in the presence of spacer unit with comparing without spacer unit.